2015
DOI: 10.1007/s10461-015-1109-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Community-Based HIV Prevention Programs in Ontario: Evidence of Effectiveness in Reducing HIV Infections and Health Care Costs

Abstract: Investments in community-based HIV prevention programs in Ontario over the past two and a half decades are assumed to have had an impact on the HIV epidemic, but they have never been systematically evaluated. To help close this knowledge gap, we conducted a macro-level evaluation of investment in Ontario HIV prevention programs from the payer perspective. Our results showed that, from 1987 to 2011, province-wide community-based programs helped to avert a total of 16,672 HIV infections, saving Ontario’s health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…What this often leads to is a policy rhetoric about community mobilization and peer leadership and the importance of combining behavioral, biomedical, and structural responses, but community and peer-led programs being funded, monitored and managed as standalone instances of generic interventions. There is conflicting evidence as to the cost effectiveness of peer led health promotion ( 23 25 ), however often omitted from the analysis is the potential community and policy system roles of peer-led programs. Moreover, cost-effectiveness studies tend to focus on direct effects rather than synergistic effects registered in other parts of the prevention system as a result of the contribution made by peer leadership activities and programs.…”
Section: Introductionmentioning
confidence: 99%
“…What this often leads to is a policy rhetoric about community mobilization and peer leadership and the importance of combining behavioral, biomedical, and structural responses, but community and peer-led programs being funded, monitored and managed as standalone instances of generic interventions. There is conflicting evidence as to the cost effectiveness of peer led health promotion ( 23 25 ), however often omitted from the analysis is the potential community and policy system roles of peer-led programs. Moreover, cost-effectiveness studies tend to focus on direct effects rather than synergistic effects registered in other parts of the prevention system as a result of the contribution made by peer leadership activities and programs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, addressing social and structural factors could significantly improve HIV prevention above individually-based biomedical and behavioral factors [17–19]. For instance, a recent economic evaluation of HIV prevention programs in Ontario, Canada found that province-wide community-based interventions that included increasing social support among residents, providing supportive housing, distributing condoms and needles and running anti-stigma campaigns, were associated with preventing 16,1672 new HIV infections, and saved the health care system approximately 6.5 billion dollars over 23 years [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Community-based HIV prevention interventions aim at supporting individuals at risk through health promotion services within de ned-geographically communities. They provide education, counselling and mass media campaigning to help their members reduce the risks of infection (14). The goal is to create a perception of community ownership where individuals become agents of change.…”
Section: Importance Of Community-based Interventions In Getting To Zero Hiv Infectionsmentioning
confidence: 99%